2020
DOI: 10.1093/cid/ciaa844
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Validation of PREDICT and Its Impact on the Transesophageal Echocardiography Use in Management of Staphylococcus aureus Bacteremia

Abstract: Background Infective endocarditis (IE) is the most feared complication of Staphylococcus aureus bacteremia (SAB). Transesophageal echocardiogram (TEE) is generally recommended for all patients with SAB, however, supporting data for this are limited. We previously developed a scoring system, “PREDICT”, that quantifies the risk of IE and identifies patients who would benefit the most from undergoing TEE. The current prospective investigation aims to validate this score. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…In our PREDICT validation cohort, we also found that patients with SAB and IE had a significantly shorter TTP than did those with SAB and no evidence of IE with a median time of 11 hr (range 8e14 hr) compared with 15 hr (11.5e18 hr) in those without IE [13]. Sensitivity of TTP at 11, 12 and 13 hr for a diagnosis of IE was 65%, 65% and 74%, respectively, whereas specificity was 75.7%, 74% and 70%, respectively, with a negative predictive value of 94%, 94% and 95%, respectively.…”
Section: To the Editorsupporting
confidence: 51%
“…In our PREDICT validation cohort, we also found that patients with SAB and IE had a significantly shorter TTP than did those with SAB and no evidence of IE with a median time of 11 hr (range 8e14 hr) compared with 15 hr (11.5e18 hr) in those without IE [13]. Sensitivity of TTP at 11, 12 and 13 hr for a diagnosis of IE was 65%, 65% and 74%, respectively, whereas specificity was 75.7%, 74% and 70%, respectively, with a negative predictive value of 94%, 94% and 95%, respectively.…”
Section: To the Editorsupporting
confidence: 51%
“…3 Including osteomyelitis, spondylodiscitis, gastroinstestinal infection, urogenital infection, airway infection, and soft tissue infection. 4 From the time positive blood culture was drawn…”
Section: Discussionmentioning
confidence: 99%
“…3 Univariate statistical analyses were performed using the Mann-WhitneyU test or the Kruskal-Wallis test. 4 Statistical analysis performed via multivariate regression analysis. 5 S. mitis indicated as baseline NBHS group in statistical analysis…”
Section: Discussionmentioning
confidence: 99%
“…A short TTP has been associated with poor outcome in bacteremia with Staphylococcus aureus [4][5][6], Streptococcus pneumoniae [7], Pseudomonas aeruginosa [8], and nontyphoid Salmonella [9]. Moreover, a short TTP is associated with an endovascular source of infection, including infective endocarditis (IE), in bacteremia with S. aureus [5,10,11]. Recently, we suggested that TTP is useful to determine the need for echocardiography in S. aureus bacteremia [12].…”
Section: Introductionmentioning
confidence: 99%